RETURN COST AND VALUE ADDED ANALYSIS OF SWEET POTATO PROCESSING (Case Study: Pasar Bengkel Village, Perbaungan District, Serdang Bedagai Regency) - Evi Fatmala (Institute of Computer Science (IOCS), 2021)
The purpose of this study was to identify how much income was obtained from processing sweet potatoes into chips and chicken claws and to identify how much value added was obtained from the chips and chicken claw business in the research area. The analytical method used is the method of income analysis with the method of calculating the Cost of Return and the method of value added analysis using the Hayami calculation method. The conclusion from the research results that the value obtained from processing sweet potatoes into chips is Rp. 4,247,914,-/ Month, while the added value of the sweet potato processing industry into chips is Rp. 1,167.37, with a value added ratio of 24.39% per month is relatively low. While the average income of chicken claw business in Delimada Village, Perbaungan District, Serdang Bedagai Regency is Rp. 4,436,460, -/ month while the added value of the sweet potato processing industry into chicken claw is Rp. 714.75, with a value added ratio of 16.42% per month is relatively low. The obstacle faced by the sweet potato processing industry in Pasar Bengkel Village, Perbaungan District, Serdang Bedagai Regency is the lack of availability of raw materials and labor.